Biofilm Formation and Phospholipase and Proteinase Production in Cryptococcus neoformans Clinical Isolates and Susceptibility towards Some Bioactive Natural Products - Borel Ndezo Bisso; Alvine Lonkeng Makuété; Joël Ulrich Tsopmene; Jean Paul Dzoyem (The Scientific World Journal)
Background. Cryptococcosis is one of the most common fungal infections in immunocompromised patients, which is caused by Cryptococcus neoformans. However, relatively little is known about the virulence factors of C. neoformans and the incidence of antifungal drug resistance in C. neoformans is rapidly increasing. This study was undertaken to investigate the virulence factors in C. neoformans, thymol, curcumin, piperine, gallic acid, eugenol, and plumbagin for their potential antimicrobial activity against C. neoformans. Methods. The production of phospholipase and proteinase was detected using standard methods. Biofilm formation was determined using the microtiter plate method. The broth microdilution method was used to determine the antifungal activity. The antibiofilm activity was assessed using the safranin staining method. Results. All isolates of C. neoformans produced biofilms with optical density values ranging from 0.16 to 0.89. A majority of C. neoformans isolates that were tested exhibited strong phospholipase (7/8) and proteinase (5/8) production. Plumbagin (with minimum inhibitory concentration values ranging from 4 to 16 μg/mL) showed the highest antifungal activity followed by thymol (with minimum biofilm inhibitory concentration values ranging from 8 to 64 μg/mL). In addition, plumbagin showed the highest antibiofilm activity with minimum biofilm inhibitory concentration and minimum biofilm eradication concentration values ranging from 4 to 16 μg/mL and 32 to 256 μg/mL, respectively. Conclusion. Plumbagin, compared to other natural products studied, was the most efficient in terms of antifungal and antibiofilm activities. Hence, plumbagin could be used in combination with antifungals for the development of new anticryptococcal drugs.